(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث عرض دراسة مسألة قابلية التحكم بالمخرجات، وكذلك قابلية الرصد للأنظمة الخطية المتقطعة ذات الأمثال الثابتة والتي تكتب على النحو التالي: وتم التوصل إلى إيجاد صيغة مكافئة للنظام الموجود أعلاه. وكذلك تم استنتاج بعض النتائج الجديدة في قابلية التحكم بالمخرجات. وكذلك تم وضع خوارزمية جديدة لإيجاد أقل عدد من الخطوات التي تمكننا من نقل النظام من الخرج الابتدائي إلى الخرج النهائي. كما تم استنتاج سلسلة من النتائج الجديدة لقابلية الرصد. وأخيراً تم وضع خوارزمية لإيجاد الحل الأمثل لمتجهة الحالة الابتدائية x(0). In this research, we investigate a problem of controllable and observable output for linear discrete-time systems of type: We have founded an equivalent formula for the linear discrete-time system. Moreover, new results of controllable output are presented. We put out a new algorithm to find the minimum number of steps that can enable us to move the output vector from the primary stage into the final one. On the other hand, necessary and sufficient observable conditions for system are derived. Finally, we put out a new algorithm to find the optimal solution for vector state x(0).